2021
DOI: 10.1021/acschembio.1c00417
|View full text |Cite
|
Sign up to set email alerts
|

Charge Assisted S/Se Chalcogen Bonds in SAM Riboswitches: A Combined PDB and ab Initio Study

Abstract: In this study, we provide experimental (Protein Data Bank (PDB) inspection) and theoretical (RI-MP2/def2-TZVP level of theory) evidence of the involvement of charge assisted chalcogen bonding (ChB) interactions in the recognition and folding mechanisms of S-adenosylmethionine (SAM) riboswitches. Concretely, an initial PDB search revealed several examples where ChBs between S-adenosyl methionine (SAM)/adenosyl selenomethionine (EEM) molecules and uracil (U) bases belonging to RNA take place. While these interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In PDB , they showed the existence of two simultaneous charge assisted Ch-bonds with an interaction energy value of −72.7 kJ mol −1 and a C−S⋯O angle of 165.2°, which is one of the major driving forces guiding the phenomena of molecular recognition. 132 Although there are numerous reports on the presence of the favourable Ch-bonding interactions in proteins using PDB analysis, yet the field remains unexplored in terms of more experimental evidence.…”
Section: Characterization Techniques Of Ncismentioning
confidence: 99%
“…In PDB , they showed the existence of two simultaneous charge assisted Ch-bonds with an interaction energy value of −72.7 kJ mol −1 and a C−S⋯O angle of 165.2°, which is one of the major driving forces guiding the phenomena of molecular recognition. 132 Although there are numerous reports on the presence of the favourable Ch-bonding interactions in proteins using PDB analysis, yet the field remains unexplored in terms of more experimental evidence.…”
Section: Characterization Techniques Of Ncismentioning
confidence: 99%
“…Some of these many applications have been reviewed recently [33,34] . Continuing research has revealed the occurrence of these bonds in biomolecules such as proteins and nucleic acids [21,35–39] or SAM riboswitches [36] . The ChB runs a full spectrum of bond strength [40] with Te being particularly strong, [41] and reveals itself in a number of ways including solid state NMR [42,43] .…”
Section: Introductionmentioning
confidence: 99%
“…This region can attractively interact with a region of high electron density in the same or a nearby molecule (nucleophilic regions) and form the so-called σ-hole interaction. , The most common examples of such interactions include hydrogen (HB), , halogen (XB), , and chalcogen (ChB) , bonds. The HB is by far the most commonly studied and employed NCI. XB and ChB donors are broadly used in organic noncovalent catalysis, drug design, and molecular recognition and in various other applications. They are relatively well-studied in crystal engineering as they provide, in contrast to HB, highly directional supramolecular assembly.…”
Section: Introductionmentioning
confidence: 99%